Ricky Ricotta's mighty robot vs. the video vultures from Venus - Pilkey, Dav, 1966- (Ricky Ricotta series, 2014)
A small mouse named Ricky Ricotta and his best friend, a giant flying robot, save the world from Victor Von Vulture and his vicious Voodoo Vultures from Venus.